Data and Information Management Tools for the CGIAR Gender and Agriculture Research Network - Mwanzia, Leroy (International Center for Tropical Agriculture, 2016)
The purpose of this webinar was to showcase how members of the CGIAR Gender and Agriculture Research Network can use two data management tools recently developed by CIAT. 1 June 2016